Nurses' Patient Safety Competencies in Aceh Province, Indonesia - Rahmad Julianto; Pratyanan Thiangchanya; Nongnut Boonyoung (Diponegoro University, 2014)
Purpose: To determine the level of nurses‟ patient safety competencies in Aceh, Indonesia. Methods: A descriptive study was conducted to randomly recruit 207 nurses in a hospital in Banda Aceh, Indonesia. The nurses‟ patient safety competencies was measured by using the Patient Safety Competencies of Nurses Questionnaire (PSCNQ) which was a self-reported, 29-item questionnaire rated on a 4-point Likert scale (1 to 4), developed based on the Canadian Patient Safety Institute‟s Safety Competencies. Result: More than half of nurses participated in the study were less than 30 years old, with a mean age of 31 years. The majority was female, married, earned diploma degree, and had working experience of 1-10 years. The overall nurses‟ patient safety competencies was at a high level. The area that nurses reported highest competency was "use personal protective equipment". Whereas the area they reported lowest competency was "maintain the documents of adverse events and report each adverse event." Conclusion: The study findings suggested that Acehnese nurse leaders should further maintain and promote nurses‟ patient safety competencies. Studies exploring factors contributing to nurses‟ patient safety competencies together with utilizing other data collection methods, such as observation is worth investigated.